2015
DOI: 10.1177/1757913915600194
|View full text |Cite
|
Sign up to set email alerts
|

Beyond cigarette smoking: smoke-free home rules and use of alternative tobacco products

Abstract: Smoke-free home rules are associated with lower current ATP use among the US population. Future research should examine whether promoting smoke-free home rules could help to reduce ATP use and related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…As per past 30 day estimates, the Eastern Mediterranean Region, reported the highest prevalence of ever use, ranging from 15.8% in Aleppo (Syria), in 2004, to 65.3% among university students in Lebanon[ 27 – 29 , 77 , 78 , 81 ]. Studies from the Region of the Americas and Europe reported much lower prevalence estimates: 11 studies from the US ranged from 1.9% to 21.8%[ 17 20 , 79 , 80 , 83 87 ], while in Europe, ever use was reported as 11.6% among adults in the UK in 2012[ 82 ], and 19.1% among adults in a subnational household survey in Israel in 2012[ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As per past 30 day estimates, the Eastern Mediterranean Region, reported the highest prevalence of ever use, ranging from 15.8% in Aleppo (Syria), in 2004, to 65.3% among university students in Lebanon[ 27 – 29 , 77 , 78 , 81 ]. Studies from the Region of the Americas and Europe reported much lower prevalence estimates: 11 studies from the US ranged from 1.9% to 21.8%[ 17 20 , 79 , 80 , 83 87 ], while in Europe, ever use was reported as 11.6% among adults in the UK in 2012[ 82 ], and 19.1% among adults in a subnational household survey in Israel in 2012[ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies from 48 countries reported regular or occasional use among adults[ 34 , 76 – 80 , 108 116 ]. Data from these studies, stratified by WHO region, are presented in Table F in S1 File .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Collins complex behavioral counseling intervention was successful at increasing bioverified quit rates for smoking mothers and concluded that implementing home smoking restrictions may be an important step in facilitating cessation [ 38 , 39 ]. The adoption of smoke-free home rules may also help reduce or prevent the uptake of alternative tobacco products [ 40 , 41 ]. Given the evidence that smoke-free home rules are associated with less airborne nicotine and lower levels of cotinine, the adoption of smoke-free home rules appears justifiable, especially as part of larger strategies to encourage cessation, but more research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Department of Health and Human Services, 2006). Furthermore, presence of smoke-free homes is associated with higher quit rates among tobacco users (Gilpin, White, Farkas, & Pierce, 1999; Hyland et al, 2009; Lee & Kahende, 2007; Mills, Messer, Gilpin, & Pierce, 2009) and possibly with decreased use of alternative tobacco products (Zhang, Martinez-Donate, Kuo, & Piper, 2016). Prevalence of personal smoke-free policies has increased over the past decades (Centers for Disease Control and Prevention [CDC], 2014; Cheng, Okechukwu, McMillen, & Glantz, 2015), with recent reports indicating that 83.0% of U.S. households have smoke-free home policies (CDC, 2014) and 78.1% have smoke-free vehicle policies (Kruger, Jama, Homa, Babb & King, 2015).…”
mentioning
confidence: 99%